Hemostasis in Endoscopic Endonasal Skull Base Surgery - Vaz-Guimaraes, Francisco; Su, Shirley Y.; Fernandez-Miranda, Juan C.; Wang, Eric W.; Snyderman, Carl H.; Gardner, Paul A. (Journal of Neurological Surgery Part B: Skull Base, 2015)
William Halsted established the basic principles of modern surgical technique highlighting the importance of meticulous hemostasis and careful tissue handling. These concepts hold true today and are even more critical for endoscopic visualization, making hemostasis one of the most relevant cornerstones for the safe practice of endoscopic endonasal surgery (EES) of the skull base. During preoperative assessment, patients at higher risk for serious hemorrhagic complications must be recognized. From an anatomical point of view, EES can be grossly divided in two major components: sinonasal surgery and sellar-cranial base surgery. This division affects the choice of appropriate technique for control of bleeding that relies mainly on the source of hemorrhage, the tissue involved, and the proximity of critical neurovascular structures. Pistol-grip or single-shaft instruments constitute the most important and appropriately designed instruments available for EES. Electrocoagulation and a variety of hemostatic materials are also important tools and should be applied wisely. This article describes the experience of our team in the management of hemorrhagic events during EES with an emphasis on technical nuances.
Keywords: endoscopic endonasal surgery; hemorrhagic complications; hemostatic techniques; surgical technique